ANALISIS KEUNTUNGAN USAHA TEMPE SUMARKO DI KELURAHAN TELING ATAS KECAMATAN WANEA KOTA MANADO - Winda Lita Theresia Porajouw; Joachim Noch Karel Dumais; Yolanda Pinky Ivanna Rori (AGRI-SOSIOEKONOMI, 2019)
The objective of this research is to analyze the profit of Tempe Sumarko Business in Teling Atas Village, Wanea Subdistrict Manado City. This research was conducted for 3 months, starting from January to March 2019. The data used in this research are primary data and secondary data. Primarydata was obtained from a direct interview with the owner of Tempe Sumarko Business. While secondary data was obtained from books available at local bookstores and the internet such as google searching to access articles from various scientific journals and thesis from other universities related to the topic of this research, especially concerning profit analysis. The results of the research indicated that Tempe Sumarko Business is profitable. The profit in December 2018 was Rp. 3.746.432,78 with the value of R/C ratio >1 which was 1,24 and the profit in January 2019 was Rp. 5.216.432,78 with the value of R/C ratio which was 1,35.*jnkd+erprm*